Participação Social no SUAS: uma análise das conferências de assistência social no governo Bolsonaro (2019-2022) - Bueno, Karina Moura (2024)
This study corresponds to an interdisciplinary and documentary research on social participation within the scope of Brazilian Social Assistance Policy. We analyze the Social Assistance conferences held during the administration of former President Jair Bolsonaro, focusing particularly on the 12th National Social Assistance Conference of 2021. We delve into the internal process of this conference, investigating this Participating Institution (PI), how access to it was granted, and how social participation was enacted, in a scenario of disputes and power relations among participants, seeking to understand the elements that impacted the conference process. Additionally, the study included in the analysis the National Democratic Social Assistance Conference of 2019 (CNDAS/19), an unofficial conference convened by civil society as a gesture of resistance after the suspension of the official process, expanding the perspective on the socio-historical-political context of the time. Furthermore, this research also considered social networks and virtual interaction, as both events included the use of digital technologies and social media. With a theoretical framework focusing on interdisciplinarity, the established objectives were: to investigate the process of the 12th National Social Assistance Conference (2021), especially regarding the mode of access of social actors and their form of participation; to examine the interaction among participants to understand the nuances of power relations in this conference process; to identify similarities and differences between the 12th National Conference of 2021 and the CNDAS/19; and finally, to contribute to the understanding of new paths for action and social participation, considering digital resources. To do so, we engaged in dialogue by bringing together authors from the Public Policy field that address social participation, such as Marcelo Kunrath Silva, Leonardo Avritzer, Rebecca Neaera Abers, Luciana Tatagiba, among others. The research revealed that, despite the institutionalization of social participation, the impact of PIs on the political scene has always varied, being influenced by the political dynamics of the sector. Thus, the 12th Social Assistance Conference demonstrated that institutionalized participatory forums were placed in a peripheral role in Social Assistance Policy. On the other hand, the CNDAS/19, although with different intentions from the official conference, proved to be a moment of mobilization, articulation, and legitimization of the identity of political actors in Social Assistance.